Comparison of Immunoglobulin G Subclass Concentrations in Severe Community-Acquired Pneumonia and Severe Pandemic 2009 Influenza A (H1N1) Infection - Gordon, Claire L. (American Society for Microbiology, 2012)
We compared immunoglobulin G (IgG) subclasses in patients with severe noninfluenza community-acquired pneumonia (CAP) to those in patients with severe pandemic 2009 influenza (H1N1) virus infection. Low IgG1 and IgG2 levels occurred often in the CAP group; however, H1N1 patients had lower IgG1 and IgG2 levels (5.4 versus 3.3 g/liter [P = 0.008] and 2.5 versus 1.2 g/liter [P < 0.001], respectively). Low IgG2 levels may be specifically linked to severe H1N1; however, it is not clear whether this association is related to H1N1 or to other features of severity.